Teaching, learning, and research in higher education : - Tennant, Mark (Routledge, 2010)
Teaching, Learning and Research in Higher Education offers a combination of critical perspectives and practical advice that is ideally suited for individuals interested in enhancing their practice through analysis and critique. The aim is to promote a critical understanding of one’s own practices: to foster personal and professional formation through a reflexive engagement with one's environment and circumstances. At a practical level this means to continuously think about how to adjust practice rather than following a formulaic approach derived from any particular educational theory. Teaching, Learning and Research in Higher Education argues that academics can find space for their own agency in the midst of institutional policies and practices that serve to frame, as well as delimit and constrain, what counts as good academic work in teaching and research. This text bridges a gap between those books that provide a high-level analysis of contemporary higher education, the more practical texts on how to be a good teacher in higher education, and those texts which aim to improve teaching through better understanding of the learning process.